2013
DOI: 10.1111/ajpy.12026
|View full text |Cite
|
Sign up to set email alerts
|

Does school suspension affect subsequent youth non‐violent antisocial behaviour? A longitudinal study of students in Victoria, Australia and Washington State, United States

Abstract: School suspension has been not only associated with negative behaviours but is predictive of future poor outcomes. The current study investigates a) whether school suspension is a unique predictor of youth nonviolent antisocial behaviour (NVAB) relative to other established predictors, and b) whether the predictors of NVAB are similar in Australia and the United States (U.S.). The data analysed here draws on two state-wide representative samples of Grade 7 and 9 students in Victoria, Australia and Washington S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…School-wide efforts also help to lessen the barrier of stigma surrounding receiving mental health supports by increasing access to services (Herrenkohl et al, 2019 ). Additionally, there is an added benefit of reducing punitive disciplinary strategies that are often sources of trauma for some students (Hemphill et al, 2013 ; Herrenkohl et al, 2019 ; Skiba et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…School-wide efforts also help to lessen the barrier of stigma surrounding receiving mental health supports by increasing access to services (Herrenkohl et al, 2019 ). Additionally, there is an added benefit of reducing punitive disciplinary strategies that are often sources of trauma for some students (Hemphill et al, 2013 ; Herrenkohl et al, 2019 ; Skiba et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Too often aggressive behaviors, especially in low-income youth of color, are subjected to disciplinary sanctions such as suspension and expulsion from school [55,56]. Out-ofschool suspension is associated with negative outcomes, such as a sense of alienation, poor academic achievement, delinquency, and substance use [57][58][59]. Schools serve as an important resource for youth in need; "commitment to school" is one of the few factors found to "buffer the effects of exposure to specific risks for violence" [60] (p. xii) and is a protective factor against antisocial/delinquent behaviors in youth.…”
Section: Implications For Practicementioning
confidence: 99%
“…This is despite the fact that these kinds of antisocial behaviour are far more common than violent antisocial behaviour. Associations between school suspension and nonviolent antisocial behaviour were examined in two different analyses of IYDS data (Hemphill et al 2012b(Hemphill et al , 2013 relating to year 7…”
Section: Suspension and Nonviolent Antisocial Behaviourmentioning
confidence: 99%
“…The second analysis examining the association between school suspension and nonviolent antisocial behaviour found that suspension was not associated with nonviolent antisocial behaviour, after including other established risk factors such as prior nonviolent antisocial behaviour, alcohol and other substance use, family conflict, poor family management, affiliation with antisocial friends, low commitment to school, and opportunities for prosocial involvement at school (Hemphill et al 2013) in the analysis. Notably, there was no association between suspension and nonviolent antisocial behaviour after the variable of interaction with antisocial friends was added into the statistical model.…”
Section: Suspension and Nonviolent Antisocial Behaviourmentioning
confidence: 99%